Obstructive sleep apnoea. (June 2016) - Manuel, Ari; Hardinge, Maxine
Abstract: Obstructive sleep apnoea occurs during sleep when there is repeated pharyngeal collapse that obstructs the airway and causes repeated awakenings from sleep. Sufferers complain of unrefreshing sleep and daytime somnolence, and bed partners usually report snoring with frequent apnoeic attacks. Problems with tasks requiring concentration, such as driving, are common, and in severe sleep apnoea the rate of road traffic accidents secondary to sleepiness is known to be high. Investigation with a sleep study is required to confirm the diagnosis and severity before the decision is made to initiate life-long treatment with nasal continuous positive airway pressure treatment. Milder cases may respond to a jaw advancement device and weight loss.